Pemanfaatan Teknologi Dalam Menigkatkan Daya Saing Usaha Homestay Di Bangka - Suci Ramadani; Mutiara Ulpa (Jurnal Penelitian Ilmu Pariwisata, 2026)
The development of digital technology has driven the emergence of new business opportunities through the utilization of creative video content on social media. This study aims to analyze creative video content as a form of digital entrepreneurship in promoting tourism in Bangka, as well as to identify opportunities, constraints, and its impact on tourists' visitation interest. The method used is a qualitative descriptive approach, with data collection conducted through in-depth interviews with content creators and tourists, observations on platforms such as Instagram and TikTok, and simple documentation. Research by Paris et al. (2025) proves that TikTok significantly influences visit intention, with a coefficient of determination (R²) of 0.655, meaning 65.5% of variation in tourist visit intention is explained by social media content. However, utilization of these opportunities is not yet optimal due to constraints such as inconsistent uploads, limited reach, production fatigue, and minimal support from the government and tourism communities. This study concludes that creative content has potential as a digital-based business that simultaneously supports tourism promotion in Bangka, and needs to be strengthened through synergy among stakeholders.